(untitled) (KULT_online, 2018)
Naomi Seidman’s book is an investigation of the love life of Jewish people in the 19th and early 20th century, specifically how it is reflected in the Jewish literature of that time. She looks at a large corpus of Yiddish, Hebrew, and Jewish-American novels and traces the processes of modernization, secularization, and Europeanization of Jewish literature and culture concerning romantic life.